System-structural approach to the analysis of game actions in team sports - Rodin, A.V.; Guba, V.P.; Bulykina, L.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate the structure and composition of game actions in team sports on the basis of the system-structural approach. Methods and structure of the study. The substantiation of the problem was carried out on the basis of scientific data obtained in 2020–2025 during research with young and qualified basketball and volleyball players (Smolensk, Voronezh, Samara, Obninsk). The research included biomechanical analysis of kinematic and dynamic characteristics under various competitive conditions, which made it possible to determine the main contours of the coordination structure of athletes’ game actions in team sports. The obtained data made it possible to substantiate the main motor components determining the competitive behaviour of a player and to construct multi-year preparation on this basis. Results and conclusions. In the theory and methodology of team sports, motor actions are examined from the perspective of the system-structural approach, which makes it possible to establish complex interrelationships of elements possessing properties inherent only to them. Technical techniques representing the external structure of game actions are not capable of independently resolving competitive tasks. Ignoring the internal side of game actions does not allow the use of these techniques in various game situations with high productivity and effectiveness.